Properties and in vitro digestibility of starch encapsulated in chitosan-sodium phytate capsules. (February 2023) - Qin, Kaili; Sun, Daiyong; Wang, Chaofan; Ji, Na; Dai, Lei; Qin, Yang; Xiong, Liu; Wang, Tao; Sun, Qingjie
Abstract: After starch is ingested by the human body, it is rapidly broken down into glucose, causing an increase in blood glucose, and high blood glucose can lead to a series of health complications. The aim of this study was to delay the digestion of starch by encapsulating it in chitosan-sodium phytate capsules. A chitosan-sodium phytate film was formed on the surface of starch granules by dropping a mixed solution of starch and chitosan into sodium phytate to form capsules, thereby inhibiting the digestion of starch by blocking amylase. At different temperatures (55–95 °C), the swelling degree of starch/chitosan capsules was 100–200% lower than that of native starch. Scanning electron microscope (SEM) images showed that the capsules consisted of starch granules covered by a chitosan-sodium phytate film. The slowly digestible starch content of starch/chitosan capsules with a chitosan-to-pea starch ratio of 1:10 was 27.72%, which was significantly higher than that of native pea starch, which was 7.97%. Further, the resistant starch content of starch/chitosan capsules with a chitosan-to-pea starch ratio of 1:5 was 15.18%, which was significantly higher than that of native pea starch, which was 6.22%. These research results are of great significance in delaying starch digestion and are suitable for patients with chronic diseases such as diabetes, cardiovascular disease, and obesity. Graphical abstract: Image 1 Highlights: A new strategy for starch encapsulated in chitosan/starch capsules was constructed. Starch granules were coated in capsules by chitosan phytate sodium films. The content of slow digestion starch in the capsules was increased. Peak gelatinization temperatures of starch encapsulated in the capsules increased.